(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
In this work we compare in the first place the Iberian onomastics with Aquitanian onomastics, considering the coincidences between full names, or the existence of names whose both elements have palallels in both languages. The existence of Iberian names formed with derivation suffixes in the same way as Aquitanian is defended. Following the same approach, we compare the Iberian onomastics with the Middle Age Basque anthroponymy.